Online Corporate Social Responsibility on Developing Countries - Virdasari, I; Soewarno, N; ., Isnalita (KnE Social Sciences, 2018)
The purpose of this paper is to examine the determinants of reporting corporate social responsibility (CSR) of the manufacturing industry in Indonesia. Particulary, it explores the impact of size, age and origin of company ownership on the online CSR reporting using the data from 100 manufacturing companies in Indonesia. The authors used the ordinary least squares regression analysis in the estimation of the influence predictive on-line corporate CSR disclosure. The findings suggest a significant positive relationship between online CSR disclosure and firm size and are insignificant company with firm age and origin. The findings are strong for different specifications. Research directed at online CSR communication between manufacturing companies. This study therefore makes an important contribution of analyzing online CSR reporting in Indonesia Keywords: Indonesia, Stakeholder Theory, Internet Reporting, Communication Strategy, Corporate Social Responsibility